ABA triblock copolymer flower micelles formulations - Almehmady, Alshaimaa (2018)
Amphiphilic polymeric materials have been used in pharmaceutical and biotechnology products for decades. These polymeric materials have grown considerably from their earlier use as surfactants, sequestering agents, drug delivery systems such as microparticles used as controlled release depots, to multifunctional polymeric micelles capable of targeting and controlling release of drugs. These generations of targeted polymeric micelles can be engineered to navigate complex biological environment, incorporate biological functionalities to achieve target specificity and control of drug concentration at tissue and cellular levels. Toward the goal to improve therapy efficacy and safety, a plethora of multivalent targeted polymeric nanocarriers fabricated from amphiphilic diblock and triblock copolymers have been investigated. Flower micelles is a type of advanced micellar architecture resulted from ABA amphiphilic triblock copolymers self-assembly. Present project focused on design, synthesis of a library of biocompatible, amphiphilic ABA triblock copolymers, based on a polyacrylate and poylacrylamide backbone, and selfassembly of these materials into flower micelles. Similar design drives the synthesis process toward precise engineering of block copolymers, therefore a combination of recently developed controlled polymerisation techniques which allowed production of uniform polymer chain and control of chain length in a reproducible quick manner have been used. A library of novel well-defined copolymers, poly(n-butyl acrylate) block-poly(Nhydroxyethylacrylamide)-block-poly(n-butyl acrylate), (n-BA)m-b-(N-HEA)nb-(n-BA)m, have been synthesised successfully using single electron transfer living radical polymerisation (SET-LRP), a 30 minutes step to yield >99% monomer conversion, and photo-induced living radical polymerisation (photoinduced LRP). Hydrophobicity can substantially influence supramolecular assembly of copolymers in aqueous environment. In this work, effect of copolymers hydrophobicity has been studied in a sub-library of copolymers in which poly(n-BA)m hydrophobic blocks length increased as follow: (n-BA)57-b-(NHEA)40-b-(n-BA)57 > (n-BA)9-b-(N-HEA)40-b-(n-BA)9 >(n-BA)3-b-(NHEA)40-b-(n-BA)3. Decreasing of polymeric micellar size was observable with increasing hydrophobic block lengths. Moreover, we found out that there is a clear relationship between copolymers cytotoxicity on Calu-3 cell line model and hydrophobicity of copolymers. Our data suggested that copolymers induce cytotoxicity by apoptotic means rather than interrupting cell membrane integrity. Covalent conjugation of active target ligands to the compositional ABA copolymers enable the formation of targeted-flower micelles. Exploiting the fact that numerous cancerous tissues are known to overexpress folate receptors, relative to normal tissues, folic acid used as active targeting ligand model. In this work, we attempted to create a folic acid-targeted flower micelle, however, conjugation data were not conclusive and therefore, no folic acid-targeted flower micelles were fabricated.